Addressing elder abuse in rural and remote communities: social policy, prevention and responses. Issue 4 (20th October 2019) - Warren, Amy; Blundell, Barbara
ABSTRACT: This article reports the findings of an international scoping literature review focussed on social policy, prevention, and service responses to elder abuse in rural and remote communities. Forty-seven articles were included in the review, and fourteen types of prevention or service responses were identified in the literature, including several Indigenous-specific initiatives. The review highlighted the need for meaningful inclusion of rural and remote communities in elder abuse policy, as well as the importance of community consultation and consideration of the local context in developing prevention and response initiatives for these communities.